Perbedaan Skor IgE Atopi Berdasarkan Jenis Kelamin pada Pasien Anak dengan Rhinitis Alergi dan Dermatitis Atopi - Manullang, Widya PS.; Riyanto, Riyanto; Sartini, Sartini; Susilo, Ferdinand (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
This study aims to investigate the relationship between gender and allergy scores in children aged 0-12 years with allergic rhinitis and atopic dermatitis. The research utilized secondary data obtained from patient medical records, comprising 32 samples with 18 males and 14 females. Data were analyzed using the non-parametric Mann-Whitney U test to evaluate the relationship between two variables: gender (binomial data) and allergy score (ordinal, interval, or ratio scale). Results indicated that U₁ was 112 and U₂ was 140. According to the Mann-Whitney critical value table with n₁=14 and U₂=18 at a 95% confidence level, the critical value was 74. Since the lowest U value (U₁ = 112) is greater than the critical value (74), H₁ is accepted and H₀ is rejected. Therefore, there is a relationship between gender and allergy scores in children aged 0-12 years with allergic rhinitis and atopic dermatitis at RSIA Stella Maris, Medan. However, the statistical analysis suggests that this relationship is weak.